Inkjet-Printed Split Ring Resonators for the Detection of Analyte Binding to a Gold Surface - Matthias Paul; Doris Pollhammer; Christoph Mehofer; Rudolf Oberpertinger; Harald Kühnel; Markus Wellenzohn (Proceedings)
This work focuses on demonstrating the working principle of inkjet-printed Au nanoparticle (NP) split-ring resonators (SRRs) as a novel platform for the detection of analytes on flexible substrates. Potential applications of this technology include rapid and reusable near-patient diagnostics. In the method, a microwave electromagnetic wave is coupled into the Au SRR via a printed Cu-NP stripline sintered photonically on a solid FR1 substrate. This coupling mechanism facilitates the detection of analytes by inducing resonance shifts in the SRR. To demonstrate the sensing principle of the platform, biomolecules are attached to the SRR and the resulting resonance shift is measured. All experiments show resonance frequency shifts in the range of approximately 20–30 MHz.